REVOLUTIONARY NATIONALISM AND EARLY STATE-BUILDING: DIVERGENT PATH OF NKRUMAH AND SOEKARNO - Pietro Fasola; Fadhli Zul Fauzi (Jurnal Politik Pemerintahan Dharma Praja, 2025)
This article presents a comparative historical analysis of postcolonial state-building under the leadership of Kwame Nkrumah in Ghana and Sukarno in Indonesia. It argues that revolutionary nationalism functioned as a double-edged force, enabling mass mobilization and political legitimacy while simultaneously generating institutional fragility in newly independent states. Employing a qualitative historical-comparative methodology and a most similar systems design, the study examines how colonial institutional legacies, bureaucratic capacity, strategies of political legitimacy, civil–military relations, social fragmentation, and Cold War geopolitics shaped divergent state-building trajectories in the two cases.The analysis shows that although both leaders pursued anti-imperialist agendas, state-led development, and mass mobilization, they adopted contrasting political strategies in response to distinct domestic and international constraints. Nkrumah relied on political centralization and a single-party system to compensate for weak administrative capacity, whereas Sukarno emphasized ideological integration and symbolic unity through Guided Democracy within a highly pluralistic social context. In both cases, however, these strategies were structurally constrained and ultimately contributed to political instability and regime collapse.The article concludes that postcolonial state-building cannot be explained by leadership charisma alone but must be understood as a product of the interaction between institutional inheritance, societal formation, political authority, and global forces.